Conservation Value of Sacred Sites of Indigenous People of the Arctic: A Case Study in Northern Russia (Conservation of Arctic Flora and Fauna (CAFF), 2004)
Working with Indigenous communities, organizations and researchers in the Yamal and Koryak Autonomous Okrugs to address conservation and cultural heritage on a large scale.